The feasibility of a weather radar near Fort McMurray, Alberta ... - Olson, S. L.; Humphries, R. G.; Barge, B. L. (University of Alberta Library, 1976)
The feasibility of a weather radar to map precipitation in the Alberta Oil Sands Environmental Research Program (AOSERP) study area near Fort McMurray, Alberta was investigated. Consultations with various groups and agencies associated with AOSERP revealed that representative precipitation data are of greatest importance to the Meteorology and Air Quality Technical Research Committee and the Hydrology Technical Research Committee. Typically, measurements are required of accumulated precipitation amounts accurate to 20 percent with spatial resolutions of four km2 • The present raingauge network may be unable to provide precipitation data with sufficient resolution and accuracy. On the other hand, careful study suggests that a radar calibrated with surface gauges may provide adequate estimates of surface precipitation. Several problems must be carefully investigated before a useful weather radar system can be realized. Of prime consequence are radar design, melting layer effects, radar location and data ...